Magnetic field enriched surface enhanced resonance Raman spectroscopy for early malaria diagnosis - Yuen, Clement (2013)
Hemozoin is a by-product of malaria infection in erythrocytes, which has been explored as a biomarker for early malaria diagnosis. We report magnetic field-enriched surface-enhanced resonance Raman spectroscopy (SERRS) of β —hematin crystals, which are the equivalent of hemozoin biocrystals in spectroscopic features, by using magnetic nanoparticles with iron oxide core and silver shell (Fe 3 O 4 @Ag ). The external magnetic field enriches β —hematin crystals and enhances the binding between β —hematin crystals and magnetic nanoparticles, which provides further improvement in SERRS signals. The magnetic field-enriched SERRS signal of β —hematin crystals shows approximately five orders of magnitude enhancement in the resonance Raman signal, in comparison to about three orders of magnitude improvement in the SERRS signal without the influence of magnetic field. The improvement has led to a β —hematin detection limit at a concentration of 5 nM (roughly equivalent to 30 parasites/μl at the early stages of malaria infection), which demonstrates the potential of magnetic field-enriched SERRS technique in early malaria diagnosis.